2023
DOI: 10.1001/jamanetworkopen.2023.36120
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune and Autoinflammatory Connective Tissue Disorders Following COVID-19

Sung Ha Lim,
Hyun Jeong Ju,
Ju Hee Han
et al.

Abstract: ImportanceMultiple cases of autoimmune and autoinflammatory diseases after COVID-19 have been reported. However, their incidences and risks have rarely been quantified.ObjectiveTo investigate the incidences and risks of autoimmune and autoinflammatory connective tissue disorders after COVID-19.Design, Setting, and ParticipantsThis was a retrospective population-based study conducted between October 8, 2020, and December 31, 2021, that used nationwide data from the Korea Disease Control and Prevention Agency CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…57 Recent studies have suggested that COVID-19 infection may trigger or exacerbate autoimmune diseases such as AAV in susceptible individuals. 12,58 In a cohort study by Lim et T A B L E 1 (Continued) significantly higher in the post-group compared to the controls. 58 There are various potential mechanisms which induce autoimmunity after COVID-19 infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…57 Recent studies have suggested that COVID-19 infection may trigger or exacerbate autoimmune diseases such as AAV in susceptible individuals. 12,58 In a cohort study by Lim et T A B L E 1 (Continued) significantly higher in the post-group compared to the controls. 58 There are various potential mechanisms which induce autoimmunity after COVID-19 infection.…”
Section: Discussionmentioning
confidence: 98%
“…12,58 In a cohort study by Lim et T A B L E 1 (Continued) significantly higher in the post-group compared to the controls. 58 There are various potential mechanisms which induce autoimmunity after COVID-19 infection. One of them is molecular mimicry, leading to the immune system falsely attacking its self-tissues when a viral protein is analogous to a protein in the body.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is a substantial body of evidence suggesting that both SARS-CoV-2 natural infection and COVID-19 vaccination (mRNA vaccines, vectored vaccines, and inactivated virus vaccines) are associated with the new onset or exacerbation of existing autoimmune and autoinflammatory conditions. [1][2][3][4][5][6][7][8][9] The question arises whether the current evidence is sufficient to confirm with postvaccination emergence of 31 cases of autoimmune conditions, including systemic lupus erythematosus (SLE), thyroiditis, Graves' disease, IgA vasculitis, inflammatory arthritis, dermatomyositis, ulcerative colitis, autoimmune hepatitis, autoimmune hemolytic anemia, autoimmune pancreatitis, ANCA vasculitis, myasthenia gravis, and Sjögren's syndrome (SS). 2 Similarly, the vectored vaccine Sputnik has also been linked to the emergence of 28 cases of autoimmune conditions in Mexico and Argentina.…”
Section: Dear Editormentioning
confidence: 99%
“…Indeed, cohort studies in Taiwan, Germany, the UK, and South Korea, published in 2023, confirmed that SARS-CoV-2 infection was associated with increased ARD morbidity. [5][6][7][8] Notably, in a German cohort of 641 704 patients with COVID-19, matched with controls, there was a 43% higher likelihood of acquiring a new autoimmune disease within 3-15 months after SARS-CoV-2 infection. 6 The COVID-19 global vaccination campaign has raised concerns over the scale of adverse outcomes and the likelihood of associated autoimmunity.…”
Section: Increasing Autoimmune Rheumatic Diseases As a Consequence Of...mentioning
confidence: 99%
“…With time passing and accumulating evidence, similar hypotheses of COVID‐19‐induced RA were tested in large studies with crystallizing a scientific fact of the association. Indeed, cohort studies in Taiwan, Germany, the UK, and South Korea, published in 2023, confirmed that SARS‐CoV‐2 infection was associated with increased ARD morbidity 5–8 . Notably, in a German cohort of 641 704 patients with COVID‐19, matched with controls, there was a 43% higher likelihood of acquiring a new autoimmune disease within 3–15 months after SARS‐CoV‐2 infection 6 …”
mentioning
confidence: 97%